2018
DOI: 10.7324/japs.2018.81002
|View full text |Cite
|
Sign up to set email alerts
|

DOE, formulation, and optimization of Repaglinide nanostructured lipid carriers

Abstract: Nanostructured lipid carriers (NLC) are a recent approach for the delivery of poorly soluble drugs with low oral bioavailability. The oral antidiabetic Repaglinide (RPG) was loaded into NLC using emulsification-ultrasonification technique. A design of experiment was constructed to study the formulation variables. The influence of the liquid lipid to the solid lipid ratio and the concentration of the surfactant on mean particle size, zeta potential, and drug entrapment efficiency was demonstrated. The mean part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It was stated in other studies that the presence of a solid lipid reduces the ζ potential values. It was also reported that there are ζ levels higher than SLNs, especially in preparations in the form of emulsions prepared with liquid lipids. …”
Section: Results and Discussionmentioning
confidence: 99%
“…It was stated in other studies that the presence of a solid lipid reduces the ζ potential values. It was also reported that there are ζ levels higher than SLNs, especially in preparations in the form of emulsions prepared with liquid lipids. …”
Section: Results and Discussionmentioning
confidence: 99%
“…The slower later release came from Apx was integrated into the NLC core and released in a sustained pattern through the matrix erosion or degradation. In contrast, the faster initial release came from Apx, rapidly diffusing from the surface [ 76 , 77 ]. Compared to the free Apx, it was clear that the optimized formula showed a slower release.…”
Section: Resultsmentioning
confidence: 99%
“…The DSC thermograms of pure GMS, SIM powder, and lyophilized NLC.1 are shown in figure 6. The pure GMS and SIM exhibit a sharp endothermic peak at 69.13 • C and 142.93 • C, respectively, which are attributed to the melting of the samples [39,67]. The thermogram of lyophilized NLC.1 shows an endothermic peak at 55.59 • C which is significantly (P < 0.05) different compared to the melting peak of pure lipid.…”
Section: Dsc Analysismentioning
confidence: 90%